The Effect of Lateral Position with Head Up 45° on Oxygenation in Pleural Effusion Patients - Endah Yuliany Rahmawati; Emmy H Pranggono; Ayu Prawesti Priambodo (Jurnal Keperawatan Padjadjaran, 2021)
Background: The accumulation of fluid in the pleural cavity will interfere with the restriction process, namely disruption of lung expansion so that the air entering the lungs is less than normal. One of the effects is shortness of breath and a decrease in oxygen saturation. In this case, nursing actions play an important role in inadequate ventilation, namely positioning. The lateral position is one of the recommended positions for patients with unilateral lung disease, one of which is unilateral pleural effusion. Position selection is very important to facilitate adequate breathing, namely one with a head-up of 45°. According to some literature, the 45° head-up position can reduce consumption and maximize lung expansion which will result in greater ventilation. Purpose: To determine the effect of the lateral position with a head-up 45° on oxygen saturation and respiratory rate in a patient with unilateral pleural effusion at the Dr. H. A. Rotinsulu Lung Hospital Bandung. Methods: The research design was a quasi-experimental design with one group pre and post-test design with a sample of 44 people. The sampling technique used consecutive sampling. The results showed that there were differences in median oxygen saturation and respiratory rate before and after the intervention. Results: The results of a comparative study using the Wilcoxon test obtained a p value of 0.0001 (p value<0.05). There is an effect of giving a lateral position with a head-up 45° on increasing oxygen saturation and decreasing respiratory rate. Conclusion: Thus, it is expected for the service unit to establish a lateral position in the direction of the effusion with a head-up of 45° as the operational standard for the management of unilateral pleural effusion impaired oxygenation patients.